ANALISIS YURIDIS TERHADAP YAYASAN YANG TIDAK MENYESUAIKAN ANGGARAN DASARNYA - Anisa, Nury (Jurnal Cakrawala Hukum, 2017)
Foundation is a legal entity consisting of wealth that is separated and destined to achieve certain goals in the field of social, religious, and humanity that has no members. Foundation is a legal institution that has binding legal force. The existence of foundations is recognized in Indonesia both before the introduction of the Foundation Law and after the Foundation Act. The Foundation in its Articles of Association in Article 71 Paragraph 4 of the Law of the Republic of Indonesia Number 28 Year 2004 regarding Amendment of Law of the Republic of Indonesia Number 16 Year 2001 regarding the Foundation argues that a foundation that has not adapted cannot carry out its activities on behalf of the foundation but becomes a associations based on the Civil Code. The foundation which does not adjust the articles of association according to the given time period is null and void and must be liquidated. With respect to null and void, the foundation is not allowed to use the word "foundation" in front of the foundation’s name which resulted in the foundation not obtaining the legal entity status and the existence degradation of the foundation’s status.